Differences in Encoding Strategy as a Potential Explanation for Age-Related Decline in Place Recognition Ability - Hilton, Christopher; Muffato, Veronica; Slattery, Timothy J.; Miellet, Sebastien; Wiener, Jan (Frontiers in Psychology, 2020)
The ability to recognise places is known to deteriorate with advancing age. In this study, we investigated the contribution of age-related changes in spatial encoding strategies to declining place recognition ability. We recorded eye movements while younger and older adults completed a place recognition task first described by Muffato et al. (2019). Participants first learned places, which were defined by an array of four objects, and then decided whether the next place they were shown was the same or different to the one they learned. Places could be shown from the same spatial perspective as during learning or from a shifted perspective (30° or 60°). Places that were different to those during learning were changed either by substituting an object in the place with a novel object or by swapping the locations of two objects. We replicated the findings of Muffato et al. (2019) showing that sensitivity to detect changes in a place declined with advancing age and declined when the spatial perspective was shifted. Additionally, older adults were particularly impaired on trials in which object locations were swapped; however, they were not differentially affected by perspective changes compared to younger adults. During place encoding, older adults produced more fixations and saccades, shorter fixation durations, and spent less time looking at objects compared to younger adults. Further, we present an analysis of gaze chaining, designed to capture spatio-temporal aspects of gaze behaviour. The chaining measure was a significant predictor of place recognition performance. We found significant differences between age groups on the chaining measure and argue that these differences in gaze behaviour are indicative of differences in encoding strategy between age groups. In summary, we report a direct replication of Muffato et al. (2019) and provide evidence for age-related differences in spatial encoding strategies, which are related to place recognition performance.